2020
DOI: 10.1088/1742-6596/1485/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Pitcher Plant (Nepenthes sp.) and Its Existence in North Sumatra Indonesia

Abstract: Nepenthes sp. is a carnivorous plant with unique shape and color shades. This unique plant has a special leaf modification called a pitcher which has the capability in catching insects and small animals. The purpose of this research was to know the types and habitat of Nepenthes sp. that found in six regencies in North Sumatra. The pitcher plants inventoried from South Tapanuli, Central Tapanuli, Humbanghasundutan, Toba Samosir, Dairi and Samosir regency in North Sumatra. The research type and method were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…The temperature factor affects the growth of Nepenthes. According to Nainggolan et al (2020) a good air temperature for N. tobaica, N. ampullaria, N. gracilis, N. rhombicaulis, N. eustachya, N. reinwardtiana x spectabilis is 20-32 o C. This research found that the air temperature in the Batu Lubang Sibolga area ranges from 22-25 o C; this means that the temperature in Batu Lubang Sibolga Area is the optimal temperature for N. gracilis and N. eustachya growth. On the other hand, soil pH is also an environmental factor that affects Nepenthes' growth.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The temperature factor affects the growth of Nepenthes. According to Nainggolan et al (2020) a good air temperature for N. tobaica, N. ampullaria, N. gracilis, N. rhombicaulis, N. eustachya, N. reinwardtiana x spectabilis is 20-32 o C. This research found that the air temperature in the Batu Lubang Sibolga area ranges from 22-25 o C; this means that the temperature in Batu Lubang Sibolga Area is the optimal temperature for N. gracilis and N. eustachya growth. On the other hand, soil pH is also an environmental factor that affects Nepenthes' growth.…”
Section: Discussionmentioning
confidence: 68%
“…Nepenthes generally grows in fairly high humidity. According to Handayani (2017), good humidity for the growth of Nepenthes is 34-80%, whereas according to Nainggolan et al (2020), optimal humidity for Nepenthes is 67-90%. In this study, the humidity in the Batu Lubang Sibolga area ranges from 90-93%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nepenthes is a member of the Nepenthaceae family. Diverse arthropod groups have been observed trapped in their pitchers on numerous occasions (Bauer et al 2015;Biswal et al 2018;Hidayat et al 2018;Rizqiani et al 2018;Setiawan et al 2018;Nainggolan et al 2020). Extrafloral nectarine glands on Nepenthes provide a scent that draws arthropods to the pitcher's lip (Bonhomme et al 2011;Gorb et al 2013;Schwallier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The pitcher plant belongs to the carnivorous plant family (Nepenthaceae) with the highest number of species, a dioecious plant, a woody or climbing plant, and a terrestrial or epiphytic plant. The plants can live in the lowlands and highlands (Moran and Clarke, 2010;Gaume et al, 2016;Thorogood et al, 2018;Scharmann et al, 2019;Nainggolan et al, 2020). The pitcher plants have an exotic pitcher with various colors and shapes, which are the evolution of the leaves (Clarke, 1997;Selviana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%